Multi-faceted role of melatonin in neuroprotection and amelioration of tau aggregates in alzheimer's disease - Balmik, Abhishek Ankur; Chinnathambi, Subashchandrabose (Journal of Alzheimers Disease, 2018)
Alzheimer's disease (AD) is one of the major age related neurodegenerative diseases whose pathology arises due to the presence of two distinct protein aggregates, viz., amyloid-beta plaques in extracellular matrix and tau neurofibrillary tangles in neurons. Multiple factors play a role in AD pathology, which includes familial mutations, oxidative stress, and post-translational modifications. Melatonin is an endocrine hormone, secreted during darkness, derived from tryptophan, and produced mainly by the pineal gland. It is an amphipathic molecule, which makes it suitable to cross not only blood-brain barrier, but also to enter several other subcellular compartments like mitochondria and endoplasmic reticulum. In this context, the neuroprotective effect of melatonin may be attributed to its role as an antioxidant. Melatonin's pleiotropic function as an antioxidant and neuroprotective agent has been widely studied. However, its direct effect on the aggregation of tau and amyloid-beta needs to be explored. Furthermore, an important aspect of its function is its ability to regulate the process of phosphorylation of tau by affecting the function of kinases and phosphatases. In this review, we are focusing on the pleiotropic function of melatonin on the aspect of its neuroprotective function in tau pathology, which includes antioxidant function, regulation of enzymes, including kinases and enzymes involved in free radical scavenging and mitochondrial protection.
Keywords: Alzheimer's disease; hyperphosphorylation; melatonin; mitochondria; Protein aggregation; tau protein

Mitochondrial cytochrome oxidase C subunit III (cox3) gene as a sensitive and specific target for molecular detection of Babesia gibsoni infection in dogs - Betgiri, Aishwarya A.; Jadhav, Sameer N.; Pawde, Mrunalini; Shukla, Anurag; Mote, Chandrashekhar; Pawar, Prashant D.; Shanmugam, Dhanasekaran; Kundu, Krishnendu (Experimental Parasitology, 2019)
A PCR targeting mitochondrial cytochrome oxidase subunit III (cox3) for molecular detection of Babesia gibsoni infection in dogs has been developed in this study. Fifty blood samples from suspected clinical cases from dogs, brought to the veterinary college clinics, were examined for presence of B. gibsoni using conventional diagnosis by microscopic examination of Giemsa stained thin blood smears. In addition, species specific PCRs targeting ITS-1 region (BgITS-1 PCR) and nested PCR targeting 18S ribosomal RNA gene (Bg18SnPCR) were carried out. A 634 bp PCR fragment of B. gibsoni cox3 gene was amplified in positive samples from three geographical locations of Satara, Wai and Pune in Maharashtra state of India. From analysis of the sequence of the B. gibsoni cox3 gene, we found that the Indian isolate had 96-98% similarity to the isolate from Japan and China. Post sequencing, de-novo diagnostic primer pair for species specific amplification of 164 bp fragment of B. gibsoni cox3 was designed and the PCR was standardized. The diagnostic results of de-novo Bgcox3 PCR were compared with BgITS-1 PCR and Bg18S nPCR. Thin blood smears detected 22% (11/50) samples positive for small form of Babesia species. The BgITS-1 PCR detected 25% samples (15/50) as positive and Bg18S nPCR detected 80% (40/50) B. gibsoni positive samples. The de-novo Bgcox3 PCR detected 66% (33/50) samples positive for B. gibsoni (at 95% CI). The analytical sensitivity of cox3 PCR was evaluated as 0.000003% parasitaemia or 09 parasites in 100 mu l of blood. The de-novo diagnostic cox3 PCR did not cross react with control positive DNA from other haemoprotozoa and rickettsia like B. vogeli, Hepatozoon canis, Trypanosoma evansi, Ehrlichia cants and Anaplasma platys. Statistically, cox3 PCR had better diagnostic efficiency than ITS-1 PCR in terms of sensitivity (p = 0.0006). No statistically significant difference between results of cox3 PCR and 18S nPCR was observed (p = 0.1760). Kappa values estimated for each test pair showed fair to moderate agreement between the observations. Specificity of Bgcox3 PCR was 100% when compared with microscopy or BgITS-1 PCR. Sensitivity of Bgcox3 PCR was 100% when compared with that of Bg18S nPCR.
Keywords: Babesia gibsoni; cox3; Diagnosis; Dog; mitochondria; molecular

Glucosinolate induces transcriptomic and metabolic reprogramming in Helicoverpa armigera - Jagdale, Shounak; Tellis, Meenakshi; Barvkar, Vitthal T.; Joshi, Rakesh S. (3 Biotech, 2021)
Glucosinolates protect plants from herbivory. Lepidopteran insects have developed resistance to glucosinolates which is well studied. However, the molecular effects of glucosinolate intake on insects are unexplored. To elucidate this, we performed transcriptomics and metabolomics of sinigrin-fed Helicoverpa armigera. Transcriptomics exhibits significant dysregulation of 2375 transcripts, of which 1575 are upregulated and 800 downregulated. Gene Ontology analysis of differentially expressed genes reveals that key hydrolases, oxidoreductases, and transferases are majorly affected. The negative impact of sinigrin is significant and localized in the endomembrane system and mitochondria. It also disturbs various biological processes such as regulation of protein metabolism and cytoskeletal organization. Furthermore, H. armigera putative myrosinase-like enzymes may catalyze the breakdown of sinigrin to allyl isothiocyanate (AITC). AITC targets the electron transport chain causing oxidative stress. KEGG pathway enrichment shows significant upregulation of oxidative phosphorylation, glutathione metabolism and amino acid metabolism. Activation of these pathways induces glutathione synthesis for sinigrin detoxification. Differential gene expression indicates upregulation of glutathione S-transferase and succinate dehydrogenase suggesting mitochondrial impact. Transcriptomics data correlated with metabolomics show changes in serine, methionine, ornithine, and other metabolite levels. It corroborates well with the transcript alterations supporting the increased glutathione production. Thus, our data suggest that sinigrin generates oxidative stress in H. armigera and insects alter their metabolic wiring to overcome sinigrin-mediated deleterious effects.
Keywords: Detoxification; Glucosinolate; Glutathione; mitochondria; Oxidative stress